Dentigerous Cysts of Jaws - J. Andrejs (Czech Dental Chamber, 2016)
Introduction, aim: Dentigerous cyst is a relatively common disease of jaws. It appears most frequently in the lower third molars area. The treatment of the disease is exclusively surgical. The aim of this study was to evaluate a group of patients diagnosed with dentigerous cyst according to the age, gender, complications, subjective complaints, localization, diagnostic procedures, type and time of the treatment. Methods: In a retrospective study, a sample of 50 patients diagnosed and treated for dentigerous cyst within five years (2008-2012) at the Department of Dentistry, Faculty of Medicine, and University Hospital in Hradec Králové, was reviewed. Conclusion: Dentigerous cysts were most frequently localised in the area of lower third mollars, the peak of occurence was in 6th decade of the life. It was more frequently diagnosed in men. Prevention and early diagnosis revealed a positive impact on the treatment duration and occurance of postoperative complications. Healing period lasted approximately 14 days in most of the patients. Only in 10.0% of pacients the healing period lasted more than four months.Postoperative complications occured mostly after removal of huge cystic lesions performed under ge-neral anesthesia. Complications were noted only in minority of outpatient procedures. In the differential diagnosis, tumors of all types must be distinguished. Histopathological examination is the only reliable method to differentiate between cysts and cystic tumors. Therefore each cystectomy must be accompanied by histopathological examination.